Determination of the absolute adsorption/desorption isotherms of CH4 and n-C4H10 on shale from a nano-scale perspective. (15th April 2018) - Liu, Yueliang; Li, Huazhou Andy; Tian, Yuanyuan; Jin, Zhehui; Deng, Hucheng
Highlights: We measure n-C4H10 adsorption on shale for the first time. n-C4H10 adsorption capacity on shale is higher than CH4 under the same condition. We use molecular simulations to determine the absolute adsorption isotherms based on excess ones. Abstract: Accurate description of absolute adsorption/desorption behavior for hydrocarbons on shale is of critical importance to the understanding of the fundamental mechanisms governing the storage, transport, and recovery of shale gas or shale gas condensate in shale reservoirs. By applying a thermogravimetric method, we first measure the excess adsorption/desorption isotherms of pure CH4 and n -C4 H10 on shale samples over the temperature range of 303.15–393.15 K. The maximum test pressures considered for CH4 and n -C4 H10 are 50 bar and 2 bar, respectively. Grand Canonical Monte Carlo (GCMC) simulations are then applied to calculate the density of the adsorption phase by considering the fluid-pore surface interactions. We use such calculated density of the adsorption phase to calibrate the excess adsorption/desorption isotherms, which enables us to eventually obtain the absolute adsorption/desorption isotherms. Such approach for estimating the density of the adsorption phase is essentially different from the commonly used approaches in which the density of the adsorption phase is considered to be independent of temperature, pressure, and pore size. The adsorption/desorption test results show that both CH4 and n -C4 H10 exhibit more adsorption as temperature decreases or pressure increases. Their adsorption/desorption isotherms exhibit hysteresis phenomenon and this phenomenon weakens as temperature increases. Comparatively, the hysteresis behavior observed for n -C4 H10 is more obvious than that for CH4 . Compared with CH4, n -C4 H10 has higher adsorption capacity under the same condition, indicating its higher affinity towards the shale with organic matters. As for the conventional approaches, the density calculated from the van der Waals constant b or the liquid hydrocarbon density can be used to reasonably well evaluate the absolute adsorption isotherms of n -C4 H10 on shale, but tends to underestimate the absolute adsorption of CH4 on shale. GCMC simulations show that the density of the adsorption phase is strongly correlated with system pressure, temperature, and pore size. Compared to the conventional approaches, GCMC simulations can better capture the in-situ density of adsorption phase; on the basis of the in-situ density of adsorption phase, we can then achieve more accurate determination of the absolute adsorption isotherms of a given hydrocarbon on shale. This study raises the imperativeness of leveraging more sophisticated simulation tools (such as GCMC) for more accurate determination of absolute adsorption isotherms.